(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2022)
Background: Neonates with Perinatal Asphyxia (PNA) are at higher risk for developing Acute Kidney Injury (AKI). Conventionally, Serum Creatinine (SCr) is used to diagnose AKI but lacks specificity during the first few days of life. Neutrophil Gelatinase-Associated Lipocalin (NGAL) has emerged as a novel biomarker of AKI in such situations, while its value in our setting is yet to be validated. The study aimed to evaluate the role of urinary NGAL (uNGAL) level as a predictive biomarker of AKI in term newborn infants with PNA. Materials and methods: This prospective observational study included 55 full-term neonates with PNA from the Special Care Neonatal Unit of Chittagong Medical College Hospital.The uNGAL was measured by an enzyme-linked immunosorbent assay. Urinary samples were obtained for uNGAL on postnatal day 1(after 6 hours), and on day 3, blood samples for sCr were obtained on postnatal day1, 3 and 6. Results: Among 55 neonates with PNA, 20 (36.4%) had AKI. The mean ±SD uNGAL level was 97.77±17.13 ng/ml in neonates with AKI compared to 25.76±2.19 ng/ml in those without AKI in the first postnatal day. An uNGAL cutoff value of 28.86 ng/ml had 90.0% sensitivity and 82.9% specificity in predicting AKI the same day. The mean value of uNGAL was observed at a lower level, 54.53±14.72 ng/ml vs 15.17±2.18 ng/ml in AKI and no AKI neonates on third postnatal days. The cutoff value for detecting AKI was seen to be 26.43 ng/ml with high validity on this day. Significant differences in sCr were observed between AKI and no AKI measuring on days one and three, whereas the difference was not significant on day six. Conclusion: The study showed that uNGAL might be a valuable biomarker for predicting AKI among neonates with PNA. JCMCTA 2022 ; 33 (1) : 173-177